2012
DOI: 10.13083/reveng.v20i2.179
|View full text |Cite
|
Sign up to set email alerts
|

Alterações Físicas E Químicas Do Solo Em Virtude De Construções Termíticas No Norte De Tocantins

Abstract: A ação dos térmitas na pastagem promove mudanças químicas e físicas que auxiliam no incremento qualitativo no solo, como aeração, aumento do teor de argila na superfície do solo e de nutrientes elaborados. Nesse sentido objetivou-se verificar as alterações ocorridas em solos sob pastagem e em termiteiros em função da atuação dos térmitas no norte do Tocantins. O diagnóstico foi realizado em Neossolo Quartzarênico órtico e Latossolo Vermelho distrófico comparando os teores de argila, silte, areia, pH, matéria o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The analysis of particle size distribution for epigeal mounds of termites in the genera Embiratermes, Velocitermes, and Orthognathotermes from pastures of the municipality of Seropédica, Rio de Janeiro (Brazil), showed an equal proportion of clay and sand particles in a high amount, but silt particles in a low amount (Lima & Pereira, 2018). Another study by Oliveira et al (2012) concerning soil contents in termite mounds belonging to genus Procornitermes in the pastures of Tocantins (Brazil) observed a high proportion of clay particles in termite mounds; the clay content was also higher than that of the adjacent soils. The high proportion of clay particles in termite mounds is probably a result of the preference of termites for fine clay particles because clay contains strong cation exchange capacity (Reddy & Perkins 1974, 1976 and is used as a cementing material for termite mounds (Donovan et al, 2001, Jouquet et al, 2004.…”
Section: -10mentioning
confidence: 98%
“…The analysis of particle size distribution for epigeal mounds of termites in the genera Embiratermes, Velocitermes, and Orthognathotermes from pastures of the municipality of Seropédica, Rio de Janeiro (Brazil), showed an equal proportion of clay and sand particles in a high amount, but silt particles in a low amount (Lima & Pereira, 2018). Another study by Oliveira et al (2012) concerning soil contents in termite mounds belonging to genus Procornitermes in the pastures of Tocantins (Brazil) observed a high proportion of clay particles in termite mounds; the clay content was also higher than that of the adjacent soils. The high proportion of clay particles in termite mounds is probably a result of the preference of termites for fine clay particles because clay contains strong cation exchange capacity (Reddy & Perkins 1974, 1976 and is used as a cementing material for termite mounds (Donovan et al, 2001, Jouquet et al, 2004.…”
Section: -10mentioning
confidence: 98%
“…Mound-building termites are consumers of dead grass residues. Thus, in pastures approaching the final degradation stages, an explosion in the termite population may occur (Oliveira et al, 2012). Furthermore, there is a large incidence of termites in soils undergoing advanced degradation stages (Oliveira et al, 2012).…”
Section: Figure 2 -mentioning
confidence: 99%
“…Thus, in pastures approaching the final degradation stages, an explosion in the termite population may occur (Oliveira et al, 2012). Furthermore, there is a large incidence of termites in soils undergoing advanced degradation stages (Oliveira et al, 2012). Boddey et al (2004) suggested that at least 50% of Brazilian pastures were in advanced degradation stages, with low grass yield and soil cover, invaded by weeds, and in many cases densely occupied by termite mounds.…”
Section: Figure 2 -mentioning
confidence: 99%